2(-7k-3)+9=

Simple and best practice solution for 2(-7k-3)+9= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(-7k-3)+9= equation:


Simplifying
2(-7k + -3) + 9 = 0

Reorder the terms:
2(-3 + -7k) + 9 = 0
(-3 * 2 + -7k * 2) + 9 = 0
(-6 + -14k) + 9 = 0

Reorder the terms:
-6 + 9 + -14k = 0

Combine like terms: -6 + 9 = 3
3 + -14k = 0

Solving
3 + -14k = 0

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -14k = 0 + -3

Combine like terms: 3 + -3 = 0
0 + -14k = 0 + -3
-14k = 0 + -3

Combine like terms: 0 + -3 = -3
-14k = -3

Divide each side by '-14'.
k = 0.2142857143

Simplifying
k = 0.2142857143

See similar equations:

| 2-144x^2= | | 7x+3y+9=0 | | -13.00+2.00=11.00 | | -6(7+2m)-8m= | | 3x/8=19 | | 2x+5=x+5+2x-70 | | -8r+27=-4(-7-r)-1 | | 3(w-1)=-12 | | 4+16x=7x+40 | | ln(9x+80)=ln(8x+71) | | 4(-7n-5)=12+4n | | 2x^2+8x-x-4=18 | | 4x+20=2x+25+x+20 | | 3x+4y=6.8 | | X-512=487 | | 40-6x=-90x+40 | | -53=n+7 | | X^2+2xy=-8 | | 9(4-6)+55= | | -15.00-2.00x=25.00 | | f(x)=5x^2+10x+3 | | -15.00-12.00x=25.00 | | 5.75=3/4x | | -7(r-9)= | | 5(2x+3)=4x-9 | | 6r+5(4r-12)= | | 7+7x=2x+32 | | 85=m-4 | | 43+10n=24n-27 | | (x-4y)dx+(x+2y)dy=0 | | 4.8/2 | | 2.5/465 |

Equations solver categories